The Release of Excitatory Amino Acids, Dopamine, and Potassium following Transplantation of Embryonic Mesencephalic Dopaminergic Grafts to the Rat Striatum, and Their Effects on Dopaminergic Neuronal Survival In Vitro - Rike Zietlow; Simon R. Sinclair; Christof J. Schwiening; Stephen B. Dunnett; James W. Fawcett (Cell Transplantation, 2002)
A major limitation to the effectiveness of grafts of fetal ventral mesencephalic tissue for parkinsonism is that about 90–95% of grafted dopaminergic neurones die. In rats, many of the cells are dead within 1 day and most cell death is complete within 1 week. Our previous results suggest that a major cause of this cell death is the release of toxins from the injured CNS tissue surrounding the graft, and that many of these toxins have dissipated within 1 h of inserting the grafting cannula. In the present experiments we measured the change over time in the concentration of several potential toxins around an acutely implanted grafting cannula. We also measured the additional effect of injecting suspensions of embryonic mesencephalon, latex microspheres, or vehicle on these concentrations. Measurements of glutamate, aspartate, and dopamine by microdialysis showed elevated levels during the first 20–60 min, which then declined to baseline. In the first 20 min glutamate levels were 10.7 times, aspartate levels 5 times, and dopamine levels 24.3 times baseline. Potassium levels increased to a peak of 33 ± 10.6 mM 4–5 min after cannula insertion, returning to baseline of <5 mM by 30 min. Injection of cell suspension, latex microspheres, or vehicle had no significant effect on these levels. We then assayed the effect of high concentrations of glutamate, aspartate, dopamine, and potassium on dopaminergic neuronal survival in E14 ventral mesencephalic cultures. In monolayer cultures only dopamine at 200 μM showed toxicity. In three-dimensional cultures only the combination of raised potassium, dopamine, glutamate, and aspartate together decreased dopaminergic neuronal survival. We conclude that toxins other than the ones measured are the main cause of dopaminergic cell death after transplantation, or the effects of the toxins measured are enhanced by anoxia and metabolic challenges affecting newly inserted grafts.